Análise da efetividade de manejo de áreas marinhas protegidas: um estudo do Parque Estadual Marinho da Pedra da Risca do Meio - Lima Filho, Joseilton Ferreira (2016)
Created as a reaction to unlimited growth of modern society over environment, protected areas are nowadays distinctive components in a world-wide conservation strategy. Many kinds of threatened ecosystems are directly benefited by them, avoiding predatory uses of its extensions due to restrictions of behaviors imposed by their establishment. Amongst these, there are maritime areas. However, as well as terrestrial spaces, the mere creation of a marine protected area does not guarantee the environment preservation. The development of efficient administrative activities is really necessary, allowing the reach of its conservation objectives, whilst benefiting the largest possible number of society sectors. Aiming to analyze the effectiveness degree of Pedra da Risca do Meio Marine State Park handling, the only marine protected area of Ceará, it was established a methodology that analysis 24 variables distributed between 7 ambits. For each ambit, it was elaborated an evaluation matrix that allows a qualification of its handling effectiveness. Integrating all evaluated sector, it was possible to measure the marine protected area’s handling effectiveness. The analysis of Pedra da Risca do Meio Marine State Park handling effectiveness resulted in a 61.46% of its excellent level, being classified as a medium satisfactory handling. It was inferred, therefore, that although it possess the basic requirement of handling, this marine protected area still have structural and administrative gaps that make it difficult to establish efficient actions in local natural resources conservation.